The competance of athletics coaches in training athletes for middle distances: study on the teams of Constantine Province, 10-14 years - ALLOUI, Mounir; HADDOUCHE, Aissa (Journal of Human Sciences, 2020)
The study aimed to find competent coaches who work with young beginners in athletics in the specialty of middle distance races in terms of training content and competition. The researcher used the descriptive method of the survey method to verify the study's hypotheses. The study sample included (37) coaches from different teams affiliated with the Constantine Athletics League who had previously trained young beginners (10-14 years old). The researcher used the questionnaire as a tool, and the spss version 20 statistical package was used to analyze the results. After analysis and discussion, the researcher concluded that many coaches are far from controlling the training content of young beginners (10-14 years), and their sports career to reach the highest level. The researcher recommended that these trainers be retrained, guided and equipped with the necessary experience and that they use modern scientific references to reach the highest levels.